Can seed quality of hairy fleabane be reduced due to glyphosate resistance? - Costa, Flávia Regina da (2018)
The resistance to glyphosate may provide a penalty on plant growth and physiology. We investigate if the resistance to glyphosate reduces the seed quality of Conyza bonariensis by performing seed viability and vigor tests under a completely randomized design with four replicates of 50 seeds for both glyphosate-susceptible (S) and -resistant (R) biotypes. Low seed viability (<50%) was found in both S and R biotypes. No difference occurred between either S and R biotypes on seed germination and embryo viability. The percentage of seed germination of the S biotype was higher than the R biotype in the cold test (~58%), accelerated aging test (~84%), and high-temperature stress test (~45%). This is the first time one found evidences that resistance to glyphosate may be responsible for a penalty on seed quality of C. bonariensis.